Injury prevention in Brazilian women's football: Perceptions of physiotherapists and practices within elite clubs - Vianna, K. B.; Ribas, L. O.; Rodrigues, L. G.; Gasparin, G. B.; Mendonça, L. D. M.; Baroni, B. M. (Physical Therapy in Sport, 2024)
Objectives To describe the perceptions of physiotherapists and the injury prevention practices implemented within elite women's football clubs in Brazil.